Beyond the CSI effect: The keys to good forensic genetics communication - Ángel Carracedo; Lourdes Prieto (Mètode Science Studies Journal: Annual Review)
Forensic genetics brings together all the genetic knowledge required to solve specific legal problems. In recent decades new techniques have shown the potential of DNA as a profiling system. These advances have arrived hand in hand with other improvements in terms of communication of test results, with the introduction of statistical evaluation. In the collective imagination, nourished by TV series such as CSI, forensic evidence is presented as one hundred percent certain, but the reality is different. However, statistical analysis has allowed us to turn from handcrafted forensic medicine based on intuition and experience, to tests based on evidence and data, where uncertainty is quantified in probabilistic terms.